Fearful versus loving parents: a cross-sectional study in Mysuru city to assess influence of parenting style on ADHD - Vadaga, Vijaylakshmi Rao; Murthy, M. R. Narayana; D., Sunil Kumar; M., Rakesh (International Journal Of Community Medicine And Public Health, 2023)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common childhood neurodevelopmental disorder. There are various genetic and social factors implicated in the development of ADHD. One of the factors is parenting style. Thus, the present study was undertaken to assess the various parenting styles present in the population and the statistical association between parenting style and ADHD prevalence. Methods: A cross- sectional study among 470 primary school students was undertaken in Mysuru district. Oral assent from students and written consent from parents was obtained for collection of data. Data was entered in MS Excel and analysed using Chi- square/Fisher’s Exact test. p<0.05 was considered to be statistically significant. Results: The present study found that majority of mothers and fathers were supportive towards their children, 260 (56.4%) and 246 (53.02%) respectively. It was found that majority of the parents 324 (68.93%) preferred to sit down and reason with their children. ADHD scores for inattention showed a statistical significance with father’s parenting style (p= 0.044). However, mother’s parenting style did not show any association with ADHD scores. Conclusions: The development of regular, structured parent management programmes would be helpful in improving parents’ knowledge about ADHD children and changing their attitudes towards them.